The effect of linguistic context on EFL vocabulary learning - Sadeghi, Karim; Nobakht, Aysan (Penerbit Universiti Kebangsaan Malaysia, 2014)
There is limited literature on the role of linguistic context in learning and remembering new vocabulary items by EFL learners. To fill this gap in literature and to further explore the relationship between surrounding linguistic context and learning, and retention of new words, this study was set out to investigate whether systematically changing the amount of surrounding context has any significant effect on learning and retention of new vocabulary items. Forty-seven Iranian female advanced EFL learners within the age range of 18-24 were employed in this study and were taught 100 new vocabulary items (unknown words) in ten sessions and in three different contextual conditions (i.e., 1. one known word, one unknown/new word; 2. two known words, one unknown/new word; and 3. three known words, one unknown/new word). Known words for contextual conditions were selected from the previous units of World Pass which the participants had covered before. Furthermore, Oxford Advanced Learner’s Dictionary was used for some of the contexts. The researchers made an attempt to use simple and high-frequency words from the units covered and/or from the dictionary. The results of one-way ANOVA for both immediate and delayed post-tests revealed that extending the number of known words (that is, adding to the amount of surrounding linguistic context) does not have any significant effect on learning and retention of new vocabulary items. It can be claimed that two or three known words context is still as small as one word context and they do not have differing contextual roles. Further results and implications are discussed in the paper.